Active antenna array for study the interaction between broadband electromagnetic oscillations and plasma - Tarasov, I.K. (Вопросы атомной науки и техники, 2009)
The active broadband antenna array is described. It consists of oscillators with the working frequencies that are close enough to the plasma frequencies. The construction of described array permits to use it as a phased array with a fast control of excited wave parameters (frequency, shape, phase velocity, amplitude). The oscillations spectrum measurements were provided and corresponding results are given in this work. The possibility of transfer into stochastic regime was also studied